Vzpostavitev slovenskega šolskega sistema leta 1919 - Protner, Edvard (Studia Historica Slovenica, 2020)
In the foreword, we outline the situation in the field of education in the Austro-Hungarian Monarchy, so that we can later in the text further analyse the goals and visions of the school reform efforts of teachers organized in local associations and two prominent pedagogical theorists. In doing so, we limit ourselves to the activities of primary school teachers and primary school legislation. In the central part of the text we describe the efforts to improve the financial and status position of teachers, the efforts to systematically reform primary education, the efforts to overcome the ideological divisiveness of the two most powerful teacher associations, and the efforts to unify teachers' associations throughout the kingdom. At the end, we outline the three most important programming texts on the reform of education in the new country and try to identify the pedagogical theoretical influences that are characteristic of the period between the two wars.
Keywords: 1919; history of education; Kraljevina SHS; reforms; SHS; Slovene education; slovensko šolstvo; šolske reforme; zgodovina šolstva